2020
DOI: 10.3390/ani10111998
|View full text |Cite
|
Sign up to set email alerts
|

Eucommia ulmoides Flavones as Potential Alternatives to Antibiotic Growth Promoters in a Low-Protein Diet Improve Growth Performance and Intestinal Health in Weaning Piglets

Abstract: Eucommia ulmoides flavones (EUF) have been demonstrated to attenuate the inflammation and oxidative stress of piglets. This study aimed to test whether EUF could be used as an alternative antibiotic growth promoter to support growth performance and maintain intestinal health in weanling piglets. Weaned piglets (n = 480) were assigned into three groups and fed with a low-protein basal diet (NC), or supplementation with antibiotics (PC) or 0.01% EUF (EUF). Blood, intestinal contents, and intestine were collected… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Eucommia flavonoids (EUF) have been shown to reduce inflammation and oxidative stress in piglets. Yuan et al. (2020) reported that EUF supplementation improved growth performance, reduced diarrhea incidence, increased villus height in the jejunum and ileum, and enhanced the abundance of lactic acid bacteria in the ileum of weaned piglets.…”
Section: Antioxidant Nutrient-targeted Mitochondrial Approachesmentioning
confidence: 99%
“…Eucommia flavonoids (EUF) have been shown to reduce inflammation and oxidative stress in piglets. Yuan et al. (2020) reported that EUF supplementation improved growth performance, reduced diarrhea incidence, increased villus height in the jejunum and ileum, and enhanced the abundance of lactic acid bacteria in the ileum of weaned piglets.…”
Section: Antioxidant Nutrient-targeted Mitochondrial Approachesmentioning
confidence: 99%
“…Additionally, Bacillus velezensis 157, isolated from EUE, exhibited antagonistic activity against a broad spectrum of pathogenic bacteria and fungi, for example, Staphylococcus aureus, Escherichia coli, Salmonella typhimurium, Clostridium perfringens, Proteus hauseri, Aeromonas hydrophila, Streptococcus agalactiae, Botrytis cinerea and Fusarium oxysporum [169]. Weaning piglets were fed with 0.01% E. ulmoides flavones (EUF) and appeared to show abundant gut microbiota and rising serum IgG levels [170]. Additionally, protocatechuic acid, extracted from E. ulmoides, increased the Firmicutes/Bacteroidetes ratio and reduced the relative abundance of Prevotella 9, Prevotella 2, Holdemanella, and the Ruminococcus torques group, and increased the relative abundance of Roseburia and Desulfovibrio in weaning piglets [171].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Although various bioactive components, such as lignans, iridoids, phenolics, steroids, terpenoids, and flavonoids have been identified in Eucommia ulmoides ( 10 ), phenolics and flavonoids, such as chlorogenic acid, protocatechuic acid, and quercetin are considered the main active components in leaves. Previous studies have found that Eucommia ulmoides flavones (EUF) could promote growth performance, improve intestinal health, and reduce colonization of coliform bacteria and diarrhea index in weanling piglets ( 11 ). Eucommia ulmoides leaf extract (EULE) has also been reported to improve the carcass traits of growing-finishing pigs and exert a lipid-lowering effect by activating the AMPK-ACC pathway and regulating mRNA expression levels related to lipid metabolism ( 12 ).…”
Section: Introductionmentioning
confidence: 99%